Synergic calculation method of voltage stability L indicator for multi-area power network. Issue 4 (3rd July 2017) - Zhang, Anan; Zhang, Fan; Li, Zhi; Li, Qian; Zhang, Xuliang; Wang, Jing
Abstract : Purpose: With the growing scale of power grids, integrated power grids often contain multiple areas. When the control centre of each regional grid conducts an assessment of local voltage stability, the calculation is always based on the local regional power grid model. However, less consideration is given to a detailed model of the entire network, which may lead to a large calculation error. Under the premise of ensuring the data and information security of Supervisory Control and Data Acquisition between different regional power grid operation control centres, the purpose of this paper is to reduce calculation error simply by using the data of a local power network. Design/methodology/approach: According to the calculation methodology of "decomposition and coordination" and the power balance equation of an interconnected power grid, an improved radial equivalent independent (REI) equivalent method, which can reflect the dynamic characteristics of interconnected power grids to a certain extent, is proposed in this paper. A mathematical model of multi-area-grid L indicator synergic computing is derived as well. Findings: With the calculation of Institute of Electrical and Electronics Engineers (IEEE) standard grids and an actual grid model, it is proven that the method proposed in this paper can significantly improve the accuracy of the regional power grid L indicator calculation and achieve the synergic computing of a multi-area power system L indicator, without an increase in data interaction among the regional power grids. Originality/value: The indicator of voltage stability among multi-area was obtained by using the improved REI equivalent method with the change of the load participation factor. Particularly, the coordinated calculation method can be implemented on a local power grid without knowledge of all the parameters of its interconnection, which can avoid possible leakage of confidential data and information of the system owners.